Splenic Vein Obstruction Due to a Solitary Echinococcal Splenic Cyst, Resulting in Gastric Fundus Varices: An Unusual Cause of Variceal Bleeding. Issue 3 (1993) - Klompmaker, I. J.; Haagsma, E. B.; Slooff, M. J. H.
Abstract : A 27-year old female patient, born and living in Morocco, suffered from severe variceal bleeding and weight loss. Eventually a diagnosis of gastrict fundus varices was made supposedly resulting from partial obstruction of the splenic vein and collateral blood flow via the short gastric veins. Splenectomy was proposed. Peroperatively it became apparent that a solitary ecchinococcal cyst in the hilus of the spleen obstructed the blood flow in the splenic vein. The cyst, the spleen, and part of the pancreatic tail were removed. After splenectomy bleeding did not recur.